2013
DOI: 10.1051/0004-6361/201218962
|View full text |Cite
|
Sign up to set email alerts
|

The distribution of warm gas in the G327.3–0.6 massive star-forming region

Abstract: Aims. Most studies of high-mass star formation focus on massive and/or luminous clumps, but the physical properties of their larger scale environment are poorly known. In this work, we aim at characterising the effects of clustered star formation and feedback of massive stars on the surrounding medium by studying the distribution of warm gas through mid-J 12 CO and 13 CO observations. Methods. We present APEX 12 CO(6-5), (7-6), 13 CO(6-5), (8-7) and HIFI 13 CO(10-9) maps of the star forming region G327.36-0.6 … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5

Relationship

5
0

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 40 publications
2
10
0
Order By: Relevance
“…Our study extends the work of Leurini et al (2013) on one source of our sample, AGAL327.293−00.579. They mapped in CO (3-2), CO (6-5), CO (7-6) and in 13 CO (6-5), 13 CO (8-7) and 13 CO (10-9) a larger area of the source than that presented here and found that, for all transitions, the spectra are dominated in intensity by the H II region rather than by younger sources (a hot core and an infrared dark cloud are also present in the area).…”
Section: Line Profilessupporting
confidence: 79%
“…Our study extends the work of Leurini et al (2013) on one source of our sample, AGAL327.293−00.579. They mapped in CO (3-2), CO (6-5), CO (7-6) and in 13 CO (6-5), 13 CO (8-7) and 13 CO (10-9) a larger area of the source than that presented here and found that, for all transitions, the spectra are dominated in intensity by the H II region rather than by younger sources (a hot core and an infrared dark cloud are also present in the area).…”
Section: Line Profilessupporting
confidence: 79%
“…G327.3-0.6 G327.3−0.6 is a hot core within a region of active star formation, and provides the longest line of sight probing the fourth Galactic quadrant in our study. Molecular emission lines give a systemic velocity of −44.5 km s −1 (San José-García et al 2013; Leurini et al 2013), and a distance of 3.3 kpc was determined via a kinematic analysis of H i absorption data (Urquhart et al 2012). OH + and o-H 2 O + show similar absorption profiles for the most part ( Figure 19).…”
Section: W3 Irs5 and W3(oh)mentioning
confidence: 99%
“…In addition to the water lines, a few lines from carbon species have been observed and are shown in Fig.13: 13 CO J=10-9, C 18 O J=9-8, and CS J=11-10. These three lines are in emission and centered at -44.8 km s −1 , hence at a slightly redshifted velocity compared to what derived Rolffs et al (2011) and Leurini et al (2013) from ground observations. Line profiles exhibit a cavity shock component of 5.3-6.5 km s −1 , but a broader component (FWHM∼11 km s −1 ) is also observed for the 13 CO J=10-9 line.…”
Section: Carbon Speciesmentioning
confidence: 45%
“…Interestingly, the emission detected in H 2 O is always redshifted compared to the 13 CO(10-9) line ( Fig. 11(b)), which was observed simultaneously to the 1113 GHz line (presented in Leurini et al, 2013). The 13 CO(10-9) seems to be associated with the absorption at ∼ −50 km s −1 and peaked at the same velocity as the CO lines observed in Leurini et al (2013).…”
Section: Hii Regionmentioning
confidence: 60%
See 1 more Smart Citation